Internalization of Religious Moderation Values in Islamic Religious Education Learning in the Era of Society 5.0 - Mu’allimah Rodhiyana; Sutiono Sutiono; Ifham Choli; Sapiudin Shidiq; Munakhiroh El Hajar (CV. Creative Tugu Pena, 2026)
The digital transformation in Islamic education presents both new opportunities and serious challenges for efforts to foster religious moderation in students. This study aims to comprehensively analyze how the digitalization of Islamic Religious Education (PAI) learning contributes to improving digital religious literacy, strengthening teacher competencies, and developing inclusive, critical, and balanced religious attitudes. Through a Systematic Literature Review (SLR) of 75 international articles indexed by Scopus and Web of Science for the period 2017–2024, this study identifies seven main trends influencing the dynamics of digital PAI learning, namely: 1) the shift of religious authority from the classroom to cyberspace, 2) digital religious literacy as a foundation for moderation, 3) expanding access to religious dialogue through online learning platforms, 4) teachers as digital moderators, 5) implementation barriers in the form of inequality in access and digital competency, 6) the need for conceptual integration between Islamic pedagogy, religious moderation, and technology, and 7) digitalization as a space for the formation of reflective religious character. This study confirms that the digitalization of Islamic education is not merely a shift in learning media but rather an epistemological transformation that necessitates a new curriculum, teacher digital competency, and robust media ethics. This research offers practical implications for schools, policymakers, and Islamic educational institutions in designing Islamic Religious Education (PAI) learning models relevant to the 5.0 era.